2013
DOI: 10.1128/jcm.01723-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Next-Generation Sequencing and Clone-Based Sequencing in Analysis of Hepatitis B Virus Reverse Transcriptase Quasispecies Heterogeneity

Abstract: We previously reported that, based on clone-based sequencing (CBS), hepatitis B virus (HBV) heterogeneity within the reverse transcriptase (RT) region was a predictor of antiviral efficacy. Here, by comparing ultradeep pyrosequencing (UDPS), i.e., nextgeneration sequencing (NGS), with CBS in characterizing the genetic heterogeneity of HBV quasispecies within the RT region, we evaluated the performance of UDPS in the analysis of HBV viral populations. HBV genomic DNA was extracted from serum samples from 31 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…1 Activation of hepatic stellate cells (HSCs) is a pivotal event in this progression. 2 Therefore, the fundamental strategy to treat liver fibrosis is to inhibit HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Activation of hepatic stellate cells (HSCs) is a pivotal event in this progression. 2 Therefore, the fundamental strategy to treat liver fibrosis is to inhibit HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of the HBV RT region, however, showed that no NA resistance-related primary mutations were found in our patients. By using ultradeep pyrosequencing in our recent published study, NA resistance-related mutations were identified more frequently in treatment-naive CHB patients than with clone-based sequencing (54). The basis for this absence of determining primary mutations might be the small number of clones (14 to 17 clones per patient) selected for sequencing, while up to 25 clones per patient were selected in our previous studies (7,54).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence could be an artificial full-length strain sequence that does not actually exist in QS. Ultradeep pyrosequencing was not suitable for determining full-length HBV sequence because of its short read (Ͻ400 bp) (26). In this study, the classic PCR amplification of the complete HBV genome by Gunther et al (10) was adopted to obtain the complete genome of a single strain, and then the PCR products were cloned and sequenced.…”
Section: Discussionmentioning
confidence: 99%